First trimester screening of serum advanced glycation end products levels of pregnant women who have risk factors for gestational diabetes and their obstetric outcomes: a preliminary case-control study. (3rd October 2022) - Gurbuz, Ozge; Yorgancı, Ayçağ; Ozgu-Erdinc, A. Seval; Tasci, Yasemin
Abstract: Advanced glycation end-products (AGE) are complex compounds formed by nonenzymatic glycosylation of proteins, nucleic acids, and lipids with glucose in the blood. We aimed to investigate whether there was a difference in first-trimester serum AGE levels of pregnant women with and without risk factors for gestational diabetes mellitus (GDM) and their obstetric outcomes. There were 44 women in study group who have risk factors for GDM and 44 as controls. Demographic features, serum AGE levels, adverse perinatal and neonatal outcomes were compared between groups. Five patients (11.4%) in the study group and one patient (2.3%) in the control group were diagnosed as GDM ( p  = .2). The serum AGE values were not statistically different between the study and control groups. There were no statistical differences between groups in terms of adverse perinatal and neonatal outcomes. However, in the group with adverse perinatal outcome ( n  = 25), AGE values were higher than the control group. The results of our preliminary study suggested that high-risk women for GDM did not have increased serum levels of AGE in the first trimester. Nevertheless, a high first-trimester serum AGE level was found to be associated with adverse perinatal outcomes. IMPACT STATEMENT: What is already known on this subject? Advanced glycation end products (AGE) are markers that are associated with diabetes and its complications. For pregnant women, a high third trimester serum AGEs levels were found in women who had gestational diabetes. What do the results of this study add? The results of our study revealed that first trimester screening of serum AGE levels of women who had risk factors for gestational diabetes was not discriminate. Nevertheless, a high first trimester serum AGE levels was associated with adverse perinatal outcome. What are the implications of these findings for clinical practice and/or further research? Whether reducing exogenous sources of AGE (western-style diet, smoking) before pregnancy will be associated with better pregnancy outcomes should be investigated in future studies.